Sustaining Digital Transformation in Faith-Based Schools: The Role of Strategic Leadership and Institutional Readiness - Aris Dwi Nugroho; Sri Ramdayeni Sakunti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to examine Islamic boarding school management strategies for responding to the challenges of the digital era, identify factors influencing technology acceptance and implementation, and explore adaptation experiences among administrators, educators, and students. This study used a multi-site qualitative case study design involving six Islamic boarding schools in Jambi Province, Indonesia. Data were collected through semi-structured interviews, non-participant observation, and document analysis, then analyzed using an interactive model that included data condensation, data presentation, and conclusion verification. The results revealed three main themes: (1) strategic digital management through institutional restructuring and administrative modernization; (2) technology acceptance influenced by policy support, infrastructure readiness, and human resource capacity; and (3) stakeholder adaptation characterized by selective technology integration while maintaining traditional learning methods such as sorogan and bandongan. This study concludes that sustainable digital transformation in Islamic boarding schools depends on strategic leadership that aligns technological advancements with religious identity. This research contributes by developing a holistic management framework that integrates digital transformation, organizational adaptation, and culturally responsive leadership in the context of Islamic educational institutions.